SOSIALISASI APLIKASI PEMANTAUAN KEPADATAN PASIEN DI RUANG INSTALASI GAWAT DARURAT RSMH PALEMBANG BERBASIS WEBSITE - Deta Mediana, Sony Oktapriandi; Deta Mediana, Mardiana (Politeknik Negeri Sriwijaya, 2024)
One of the roles of technology is to provide convenience in public services. RSMH Palembang's Emergency Department (IGD) section strives to provide medical services by providing fast and precise treatment for patients with emergency conditions by utilizing technology. Based on field surveys, the problems that occur are overcrowding and accumulation of patients in the Emergency Unit, so the aim of this activity is how to monitor patient density based on a website. With real-time monitoring, the quality of service to patients can be improved. The activity carried out was by providing outreach to RSMH Palembang partners. The final result of this activity was that the partner team experienced ease of use of the web-based application for monitoring patient density in the Emergency Unit by 80%, clarity of features by 85% and partner understanding of using the web-based application by 85 %.